ILMU KALAM: BAGAIMANA PENDIDIKAN JASMANI DALAM PERSPEKTIF HADIS - Thesya Alda Nia; Ahmad Nasrulloh; Sigit Nugroho; Elsa Ariestika (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
Physicalieducationiisianiintegralipartiofioverallieducation.iPhysicalieducationiisinotionlyirelateditoiphysicalidevelopmentibutiisicloselyirelateditoispiritualiandimentalihealth. This study examines the perspective of physical education in hadith. Theimethodiusediisitheimethodioficontentianalysisi (content analysis). Theidata were collected using a bibliography study and arranged theiorderiofitheidata, organizingiit intoiaipattern, categoryiandibasiciunitiof description. In this case, after the researcher has succeeded in obtaining data and information from theiobject underistudy, the steps taken are then presented in full without adding or subtracting information on matters relating to the objectiofiresearch. TheiresultsiofithisistudyiindicateithatitheiProphet's Hadith is a source and inspiration for Islamic education containing instructions that regulate all activities of the Muslim community. As a source of Islamic education, the Prophet's hadith is loaded with various educational concepts, including the concept of physical education. Physical education is not only limited to fostering physical aspects, more than that, physical education is a tool/means for students to instill social and moral values such as loyalty, dedication, team work, honesty, justice and responsibility, unity, friendship, perseverance, hard work and dedication. sportsmanship.